2014
DOI: 10.1111/echo.12636
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantitative Wall‐Motion Analysis and Strain for Detection of Coronary Stenosis with Three‐Dimensional Dobutamine Stress Echocardiography

Abstract: Background Quantitative analysis of wall motion from three-dimensional (3D) dobutamine stress echocardiography (DSE) could provide additional diagnostic information not available from qualitative analysis. In this study we compare the effectiveness of 3D fractional shortening (3DFS), a measure of wall motion computed from 3D echocardiography (3DE), to strain and strain rate measured with sonomicrometry for detecting critical stenoses during DSE. Methods Eleven open-chest dogs underwent DSE both with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…They found that the discriminative power for the detection of regional myocardial abnormality was highest for circumferential strain with automated function imaging. In another study, Parker et al performed a dobutamine stress echocardiography study for the detection of critical stenoses and compared the efficacy of 3D fractional shortening measured by 3D echocardiography with strain and strain rate obtained from sonomicrometry. Similar sensitivity, specificity, and area under the curve values were found for 3D fractional shortening, area strain, and circumferential strain and strain rate, but those for longitudinal strain and strain rate were found to be less specific.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the discriminative power for the detection of regional myocardial abnormality was highest for circumferential strain with automated function imaging. In another study, Parker et al performed a dobutamine stress echocardiography study for the detection of critical stenoses and compared the efficacy of 3D fractional shortening measured by 3D echocardiography with strain and strain rate obtained from sonomicrometry. Similar sensitivity, specificity, and area under the curve values were found for 3D fractional shortening, area strain, and circumferential strain and strain rate, but those for longitudinal strain and strain rate were found to be less specific.…”
Section: Discussionmentioning
confidence: 99%
“…The developed tools of automated analysis of three‐dimensional stress echocardiography may provide useful quantitative and objective parameters to assist the clinical expert in the diagnosis of left ventricular function . Four‐dimensional echocardiography area strain, the fractional change in the area of the sonomicrometer triangle (Area ES ‐Area ED )/Area ED , equal to longitudinal strain multiplication by circumferential, was a novel strain parameter comprehensively derived from longitudinal strain and circumferential strain, has incremental value for the diagnosis of CAD in patients or animal model with severe coronary artery stenosis at rest . But the diagnosis value of area strain in patients with mild coronary artery stenosis remained uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The MYDISE (myocardial Doppler in stress echocardiography) study has achieved the improvement in sensitivity by means of tissue Doppler‐derived quantitative DSE. Whether other quantitative analysis such as two‐dimensional or three‐dimensional strain rate imaging can complement the sensitivity of DSE is still controversial. In the present study, a THC score of ≥2 on baseline echocardiography can predict the presence of myocardial ischemia with a sensitivity of 64% and a specificity of 65%.…”
Section: Discussionmentioning
confidence: 99%